2014
DOI: 10.1088/1742-5468/2014/02/p02020
|View full text |Cite
|
Sign up to set email alerts
|

Fractal and multifractal properties of a family of fractal networks

Abstract: In this work, we study the fractal and multifractal properties of a family of fractal networks introduced by Gallos et al. ( Proc. Natl. Acad. Sci. U.S. A., 2007, 104: 7746). In this fractal network model, there is a parameter e which is between 0 and 1, and allows for tuning the level of fractality in the network. Here we examine the multifractal behavior of these networks, dependence relationship of fractal dimension and the multifractal parameters on the parameter e. First, we find that the empirical fracta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 40 publications
0
42
0
Order By: Relevance
“…In contract to a "monofractal" with geometrical parameters determined by only one fractal dimension d, the spectrum of generalized fractal dimensions of a multifractal (inhomogeneous fractal) determines some structural and statistical properties of the system. The theory of multifractals attracts attention of researches engaged in various fields of physics and mathematics because analysis of experimental results suggests that many systems exhibit multifractal behav ior [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Multifractal Analysismentioning
confidence: 99%
“…In contract to a "monofractal" with geometrical parameters determined by only one fractal dimension d, the spectrum of generalized fractal dimensions of a multifractal (inhomogeneous fractal) determines some structural and statistical properties of the system. The theory of multifractals attracts attention of researches engaged in various fields of physics and mathematics because analysis of experimental results suggests that many systems exhibit multifractal behav ior [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Multifractal Analysismentioning
confidence: 99%
“…Song et al [30] developed a method for calculating the fractal dimension of a complex network by using a box-covering algorithm and identified self-similarity as a property of complex networks [31]. Moreover, a myriad of algorithms and studies on networks' multifractal analysis have been proposed and developed lately [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Jung [43] found that MFA is the best tool to describe the probability distribution of the clustering coefficient of a complex network. Some algorithms have been proposed to calculate the mass exponents τ (q) and to study the multifractal properties of complex networks [44][45][46][47]. Based on the compact-box-burning algorithm for fractal analysis of complex networks which is introduced by Song et al [5], Furuya and Yakubo [44] proposed a compact-box-burning (CBB) algorithm for MFA of complex networks and applied it to show that some networks have multifractal structures.…”
mentioning
confidence: 99%
“…Wang et al [45] proposed a modified fixed-size boxcounting algorithm to detect the multifractal behavior of some theoretical and real networks. Li et al [46] improved the modified fixed-size box-counting algorithm [45] and used it to investigate the multifractal properties of a family of fractal networks introduced by Gallos et al [48]. We call the algorithm in Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation